Countercyclical, COVID-19, and Financial Distress of Rural Bank Setting the Agenda for the Post Covid-19’s Stimulus - Wulandari, Putu Vera; Darma, Gede Sri; Mahyuni, Luh Putu (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 2 Tahun 2022DO - 10.24843/MATRIK:JMBK.2022.v16.i02.p09, 2022)
This study aims to determine Countercyclical, COVID-19, and Financial Distress of Rural Bank Setting the Agenda for the Post Covid-19's Stimulus. The research design used in this study is an associative design. This study uses two approaches, namely qualitative and quantitative approaches. This study, in addition to examining the effect of the independent variables (ROA, CAR, and NPL) on the dependent variable (Financial Distress) which is moderated by the moderating variable (GCG). The sample in this study was 134 rural banks in Bali. Bali was chosen because Bali was most affected by the Covid-19 pandemic because the tourism MSME sector is the main economy in Bali. The result of this study is Profitability (ROA) has a significant negative effect on Financial Distress. CAR has a significant negative effect on Financial Distress. NPL has a significant positive effect on Financial Distress. GCG is a Quasi Moderation variable. GCG strengthens the negative effect of ROA on financial distress.  GCG weakens the effect of CAR on financial distress. GCG does not moderate the effect of NPL on Financial Distress